Non-Invasive Ventilation in Acute Exacerbations of COPD: A Systematic Review and Meta-Analysis of Mortality, Morbidity, and Hospital Outcomes - Alniazi, Racha; Abdul Ghani, Sheikh; Imtiaz, Natasha; Muhammad Ibrar; Ajmal, Laiba; Khadija, Nawal; Sarmad Al Hamdani, Mustafa; Kumar, Pershan; Khan, Muhammad Shaheer; Abdul Jabbar, Rammal (Indus Journal of Bioscience Research, 2025)
Background: Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is one of the major causes of hospitalization, respiratory failure and mortality globally. Non-invasive ventilation (NIV) has continuously taken a leading position in terms of reducing intubation, intensifying gaseous exchange, and improving surpassed. However, more recent comparisons of NIV versus any other interventions have demonstrated that it remains unclear as to its effectiveness insofar as our clinical outcome is concerned, including that of high-flow nasal cannula (HFNC), or other NIV techniques. Objectives: The purpose of this systematic review and meta-analysis was to assess the effect of NIV on mortality, risk of intubation, or hospital outcomes among patients who were admitted due to exacerbations of acute COPD. Methodology: We performed a meta-analysis and systematized review following PRISMA. PubMed, Embase, Cochrane Central and Scopus were searched until December 2024. Randomized controlled trials (RCTs) of NIV versus standard medical therapy, Oxygen supplementation or HFNC were thought to be eligible. Mortality and morbidity (intubation, failure of treatment) were the major outcome measures. Hospital and ICU length of stay were the secondary outcomes. Two reviewers independently extracted a set of data on which pooled estimates were calculated through a random-effects model. The number of included RCTs was seven (n = 1,466 patients). Results: The analysis included seven randomized controlled trials, including a total of 1,466 patients with exacerbation of COPD. The use of non-invasive ventilation (NIV) was linked to in-hospital mortality rate reduced significantly as compared to the conventional medical treatment (relative risk [RR] 0.58, 95% CI: 0.420.79, p < 0.001). NIV also decreased morbidity outcome, lower intubation requirement (RR=0.47, 95% CI: -3.0 to -1.2, p < 0.001), and better hospital outcomes outcome (mean length of stay was shorter by 2.1 days, 95% CI: 0.36- 0.62, p < 0.001). The readmission rates were slightly decreased, but the outcomes were different in studies. There was no data of augmented negative events, which proved the safety of NIV in this group. Conclusion: This meta-analysis validates that NIV greatly decreases both morbidity and risk of intubation in AECOPD with evident survival advantage in previous RCTs. The differences in mortality are less significant in recent comparisons to HFNC, but NIV is still more effective in avoiding a failure in the treatment process. Mixed outcomes are observed with regard to hospital outcomes that include length of stay. NIV is a significant part of treatment particularly in acute hypercapnic respiratory failure yet further studies are necessary to maximize patient selection.